A Subclass of Harmonic Functions Related to a Convolution Operator - Saqib Hussain; Akhter Rasheed; Maslina Darus (Journal of Function Spaces)
We introduce a new subclass of harmonic functions by using a certain linear operator. For this class we derive coefficient bounds, extreme points, and inclusion results and also show that this class is closed under an integral operator.